Why are there so few basin-wide treaties? Economics and politics of coalition formation in multilateral international river basins. Issue 4 (19th May 2019) - Dinar, Ariel; De Stefano, Lucia; Nigatu, Getachew; Zawahri, Neda
ABSTRACT: Examinations of international water treaties suggest that riparian states are not heeding the advice to adopt IWRM. Theories suggest that the larger the number of negotiating states, the lower the cost (per state) of the joint operation of treaties, but the higher the transaction costs of negotiating and maintaining them. We model the trade-off between benefits and costs associated with the number of treaty signatories and apply it to a global treaty data-set. Findings confirm that the transaction costs of negotiation and the economies of scale are important in determining the paucity of basin-wide agreements, the treaties' content and their extent.